2008
DOI: 10.1186/1471-244x-8-74
|View full text |Cite
|
Sign up to set email alerts
|

Predicting violent infractions in a Swiss state penitentiary: A replication study of the PCL-R in a population of sex and violent offenders

Abstract: Background: Research conducted with forensic psychiatric patients found moderate correlations between violence in institutions and psychopathy. It is unclear though, whether the PCL-R is an accurate instrument for predicting aggressive behavior in prisons. Results seem to indicate that the instrument is better suited for predicting verbal rather than physical aggression of prison inmates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
(42 reference statements)
1
8
0
4
Order By: Relevance
“…In a study carried out in seven British prisons, Hare, Clark, Grann, and Thornton () found that PCL‐R scores significantly predicted future acts of violent assault, although the predictive ability of PCL‐R scores was weaker than that of previous convictions or age. In contrast, according to a study conducted in a single Swiss prison, the only significant prediction produced by PCL‐R scores was between PCL‐R Factor 1 scores and verbal violence (Endrass, Rossegger, Urbaniok, et al, ), and a study in prisons in the southeastern United States found that PCL‐R scores did not predict any form of misconduct (Walters, Duncan, & Geyer, ). In the case of the VRAG, a study in a Swiss prison showed that VRAG scores moderately predicted both verbal and physical violence, but for sex offenders only (Endrass, Rossegger, Frischknecht, et al, ).…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study carried out in seven British prisons, Hare, Clark, Grann, and Thornton () found that PCL‐R scores significantly predicted future acts of violent assault, although the predictive ability of PCL‐R scores was weaker than that of previous convictions or age. In contrast, according to a study conducted in a single Swiss prison, the only significant prediction produced by PCL‐R scores was between PCL‐R Factor 1 scores and verbal violence (Endrass, Rossegger, Urbaniok, et al, ), and a study in prisons in the southeastern United States found that PCL‐R scores did not predict any form of misconduct (Walters, Duncan, & Geyer, ). In the case of the VRAG, a study in a Swiss prison showed that VRAG scores moderately predicted both verbal and physical violence, but for sex offenders only (Endrass, Rossegger, Frischknecht, et al, ).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Studies in Spain (Arbach‐Lucioni, Martinez‐García, & Andrés‐Pueyo, ) and Taiwan (Kuo, Cuvelier, & Huang, ) reported similar US average rates of prisoner‐to‐prisoner physical violence (8%), but the Taiwan study showed a much higher rate of prisoner‐to‐prisoner psychological violence (21%). According to two studies based on records from a single Swiss prison, 28% of prisoners said they had been victims of prisoner‐to‐prisoner physical violence, 26% had been subject to verbal violence, and 15% had taken illegal drugs during their incarceration (Endrass, Rossegger, Frischknecht, Noll, & Urbaniok, ; Endrass, Rossegger, Urbaniok, Laubacher, & Vetter, ). More recently, a 1‐year survey of a Swiss pre‐sentencing prison found that 30% of inmates had reported being victims of prisoner‐to‐prisoner physical violence (Pont et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mean PCL-R value in the Aix la (Molto, Poy, & Torrubia, 2000), 15.3 in an English study (Coid et al, 2009), in Switzerland just 12 (Endrass, Rossegger, Urbaniok, Laubacher, & Vetter, 2008), and 12 in a German sample of prisoners in West Berlin (Dahle, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Jedoch dürfen die bedeutung und die aussagekraft selbst sorgfältig abgeklärter Werte nicht überschätzt werden, denn im deutschsprachigen raum besteht das Problem, dass in Straftäterpopulationen ein Durchschnittswert der PCl-Scores von 12 vorliegt [19,20]. Damit liegt ein großteil der Strafgefangenen in Deutschland und der Schweiz weit unter dem "Psychopathy"-grenzwert von 30.…”
Section: Andere Verfahrenunclassified